The Mediation Effect of Financing Mix on Investment Opportunity Set and Profitability Relationship - Yuliani, Yuliani; Fuadah, Lukluk; Thamrin, Kms Husni (Ekspektra : Jurnal Bisnis dan Manajemen, 2018)
This study aims to provide empirical evidence about the effect of investment opportunity set (IOS) on profitability and the role of financing mix as mediating the influence of IOS on profitability. The type of research is explanatory research with survey method. The units of analysis aremedium indutrial’s company and large industrial’s companyin Palembang Citywhich the respondents areowner, financial manager and finance staff of 56 people. Collecting the data start from August to September 2017. Data type is primary through questionnaire. The method of data analysis is Partial Least Square (PLS). The research findings that IOS is not significant affect to profitability while financing mix acts as a perfect mediation of IOS influence on the profitability of industrial companies in Palembang City.Pengaruh Mediasi Bauran Pendanaan Terhadap Hubungan Set Peluang Investasi dan ProfitabilitasAbstrakPenelitian ini bertujuan untuk memberikan bukti empiris tentang pengaruh set kesempatan investasi (IOS) terhadap profitabilitas dan peran campuran pembiayaan sebagai mediasi pengaruh IOS terhadap profitabilitas. Jenis penelitiannya adalah explanatory research dengan metode survei. Unit analisis aremedium perusahaan indutrial dan perusahaan industri besar di Kota Palembang adalah responden, pemilik keuangan dan staf keuangan sebanyak 56 orang. Mengumpulkan data mulai dari bulan Agustus sampai September 2017. Jenis data adalah primer melalui kuesioner. Metode analisis data adalah Partial Least Square (PLS). Temuan penelitian bahwa IOS tidak berpengaruh signifikan terhadap profitabilitas sedangkan campuran pembiayaan berperan sebagai mediasi sempurna pengaruh IOS terhadap profitabilitas perusahaan industri di Kota Palembang.